Problematic use of prescription-type opioids prior to heroin use among young heroin injectors - Pollini RA, Banta-Green CJ; Cuevas-Mota J; Metzner M; Teshale E; Garfein RS (Substance Abuse and Rehabilitation, 2011)
Robin A Pollini1, Caleb J Banta-Green2, Jazmine Cuevas-Mota3, Mitcheal Metzner3, Eyasu Teshale4, Richard S Garfein31Pacific Institute for Research and Evaluation, Calverton, MD; 2Alcohol and Drug Abuse Institute, University of Washington, Seattle, WA; 3Department of Medicine, University of California San Diego, La Jolla, CA; 4National Center for HIV/AIDS, Viral Hepatitis, STD and TB Prevention, Centers for Disease Control and Prevention, Atlanta, GA, USABackground: Misuse of prescription-type opioids and related adverse health effects are increasing, but little is known about the role of these drugs as a precursor to heroin use. We conducted an exploratory study to determine the proportion of young heroin injectors reporting problematic use of prescription-type opioids prior to using heroin, and to describe the factors associated with prior problematic prescription-type opioid use.Methods: Between March 2009 and June 2010, we recruited injection drug users (IDUs) for a cross-sectional study of hepatitis C virus infection risk. Participants were aged 18–40 years and had injected illicit drugs within the previous six months. A computerized self-administered survey assessed sociodemographics, drug use history, human immunodeficiency virus (HIV)/hepatitis C virus risk behaviors and perceptions, and medical history. We added questions on prescription-type opioid use to the parent study in March 2010; heroin injectors who subsequently enrolled and reported problematic prescription-type opioid use prior to heroin initiation were compared with other heroin IDUs using univariate and multivariate regression methods.Results: Among 123 heroin IDUs, 49 (39.8%) reported problematic prescription-type opioid use prior to heroin initiation (“prescription-type opioid first injection drug users” (PTO-First IDUs)). PTO-First IDUs had higher odds of injecting with friends (adjusted odds ratio [AOR] 6.01; 95% confidence interval [CI] 1.90–19.07), getting new syringes from a spouse/family member/sex partner (AOR 23.0; 95% CI 2.33–226.0), knowing about the local syringe exchange program (AOR 7.28; 95% CI 1.17–45.05), using powder cocaine (AOR 3.75; 95% CI 1.43–9.86), and perceiving themselves as less likely than other IDUs to get HIV (AOR 4.32; 95% CI 1.26–14.77). They had lower odds of ever being tested for HIV (AOR 0.25; 95% CI 0.08–0.80).Conclusion: A high proportion of young heroin IDUs reported problematic prescription-type opioid use prior to initiating heroin use. Our study provides several avenues for future investigation to help further characterize this subset of IDUs and their risks and perceptions related to HIV and other blood-borne pathogens.Keywords: injection drug users, prescription-type opioids